Laws, policy measures, standards and regulations in the water sector in Lebanon: a review and perspective - Chatila, Jean G. (2003)
Lebanon is increasingly suffering from shortage and mismanagement of water, which is becoming a commodity of considerable value due to the inadequacy of supply to meet the needs of potential users. Efficient solutions for water-related problems necessitate the adoption of well-planned policies. These policies should concentrate on improving water management, rationalizing water consumption, and augmenting and protecting water supplies. Strict water policy, wastewater treatment and disposal criteria should be in effect in order to avoid contamination and achieve proper management of water resources systems. A system of laws and policies has been developed or under development, in which the government has framed comprehensive codes and regulations including health standards. In this instance, this paper describes different aspects of the laws and applicable policies in the water sector in Lebanon. A set of proposed regulations and recommendations has been developed.